Penerapan Pancasila dalam Kehidupan Sehari - Hari di Lingkungan Mahasiswa Usia 19-20 Tahun - Ayu Praba, Laras Dinda; Putri, Aurora Saskia; Amanda Zebua, Naomi Lifanya; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Pancasila is the foundation of the Indonesian state which plays an important role in shaping the character and behavior of society, including in the student environment. This study aims to identify the application of Pancasila values ​​in the daily lives of students aged 19-20 years. The study was conducted with a quantitative descriptive approach through data collection using a Google Form-based questionnaire. The results of the study are expected to provide an overview of the extent to which Pancasila values, such as mutual cooperation, tolerance, and social justice, are applied in the lives of students. In addition, this study also aims to analyze the factors that influence the application of these values. The findings of this study are expected to contribute to efforts to strengthen Pancasila education among students.